Lean construction: verificação da implantação dos princípios em obras verticais no município de São Paulo - SP - Silveira, Bruna Ambrozim (2017)
The present study aims to verify if the Lean Construction practices are applied totally or partially in projects related to the civil construction sector, in the city of São Paulo - SP. This work has a qualitative approach, for exploratory and descriptive purposes, using the Multiple Case Study procedure. In order to carry out this work, two companies with headquarters in São Paulo - SP, Company A and Company B, were analyzed. For the verification of the practices of the philosophy Lean Construction in companies A and B, interviews were conducted with the technical directors, managers and workers, using a questionnaire containing the eleven principles of Lean Construction proposed by Koskela (1992). With the realization of this study, it was observed that even without full knowledge of the principles of Lean Construction, some practices are carried out in accordance with the philosophy, however it was evidenced that there is a need to disseminate the concepts of this philosophy to be applied with more efficiency in the market.